Design of Reconfigurable Metasurface Antenna for 6G in sub-THz band - Wijaya, Harly (Cattleya Darmaya Fortuna, 2025)
We propose and evaluate a reconfigurable metasurface antenna at D band (f₀≈140 GHz) for short-range 6G applications. The main problem is in sub-THz.—High FSPL, component losses, and beam steering limitations are addressed through a loss-aware co-design that integrates unit-cells (2-bit MEMS and continuous LC), feed/illumination, and radiation-friendly bias networks, along with multi-objective beam codebook optimization (gain maximization, SLL minimization, and scan loss). Full EM simulation results on a transmitarray (TA) architecture show dB at 134–146 GHz (≈8.6%), realized peak gain of 31.8 dBi (aperture efficiency 38–43%), best SLL of −14.1 dB, beam pointing error ≤1.1°, and beam steering up to ±40° with worst-case scan loss of 3.4 dB; the LC variant provides more precise pointing (≈0.4°). Compared to the reflectarray baseline, TA excels in wide scans due to minimal feed blockage. Link-level estimations show support for 64-QAM (10–30 m) and 256-QAM (10–20 m) under LOS conditions. This approach validates the feasibility of an efficient and realizable sub-THz reconfigurable antenna for 6G extreme